2010
DOI: 10.1108/13620431011094050
|View full text |Cite
|
Sign up to set email alerts
|

The role of personality in the job demands‐resources model

Abstract: PurposeThe central aim of this study is to incorporate two core personality factors (neuroticism and extroversion) in the job demands‐resources (JD‐R) model.Design/methodology/approachIt was hypothesized that neuroticism would be most strongly related to the health impairment process, and that extroversion would be most strongly related to the motivational process. The hypotheses were tested in a sample of 3,753 Australian academics, who filled out a questionnaire including job demands and resources, personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 25 publications
6
76
0
1
Order By: Relevance
“…This two-stage process is known as “ health impairment ” or “ energetic process ,” and it is embedded in the Job Demands Resources (JD-R) model (Demerouti et al, 2001) and empirically supported (Bakker et al, 2004, 2010; Bakker and Demerouti, 2007; Xanthopoulou et al, 2007; Hakanen et al, 2008; Demerouti and Bakker, 2011; Schaufeli and Taris, 2014). Considering research in support of this model, it is likely that the health impairment reflects a more universal process at work, of which the health issue is just one symptom (Balducci et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This two-stage process is known as “ health impairment ” or “ energetic process ,” and it is embedded in the Job Demands Resources (JD-R) model (Demerouti et al, 2001) and empirically supported (Bakker et al, 2004, 2010; Bakker and Demerouti, 2007; Xanthopoulou et al, 2007; Hakanen et al, 2008; Demerouti and Bakker, 2011; Schaufeli and Taris, 2014). Considering research in support of this model, it is likely that the health impairment reflects a more universal process at work, of which the health issue is just one symptom (Balducci et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it appeared that personality traits, in addition to their direct effect on work engagement, also played a role in the way workers perceive their work environment. A study conducted by Bakker, Boyd, Dollard, Gillespie, Winefield, & Stough (2010) showed that neuroticism was related to the perception of higher job demands, whereas extraversion was related to the perception of higher job resources in a sample of academics. These results suggest that individuals who are more prone to experience negative emotions could perceive their work environment as insecure and uncomfortable and, consequently, may have difficulties in experiencing work engagement or occupational commitment.…”
Section: Work Engagement and Personalitymentioning
confidence: 99%
“…To test the models, we included the latent variables job resources (represented by social support from colleagues, autonomy, and opportunities for development), job demands (represented by work pressure, emotional workload, and physical workload), work engagement (represented by vigor, dedication, and absorption), emotional exhaustion (represented by four manifest items), and career competencies (represented by reflection on motivation, reflection on qualities, networking, self-profiling, work exploration, and career control). This procedure has been used in several studies testing the JD-R model (e.g., Bakker et al, 2010;. Table 1 shows the means, standard deviations, and intercorrelations of the study variables.…”
Section: Strategy Of Analysismentioning
confidence: 99%